2020
DOI: 10.1002/fsn3.1619
|View full text |Cite
|
Sign up to set email alerts
|

Laxative and antioxidant effects of ramie (Boehmeria nivea L.) leaf extract in experimental constipated rats

Abstract: Ramie leaf ( Boehmeria nivea L.) is rich in cellulose, polyphenol compounds, vitamin C, and minerals. The leaves of this plant, which are used for medicinal purposes, have long been reported to have anti‐inflammatory, antioxidant, anticolitis, and antidiabetic effects. We investigated the protective effects of ramie leaf ethanol extract (RLE) against loperamide‐induced constipation and oxidative stress in rats. Male Sprague‐Dawley rats were administered 200 or 400 mg/kg body weight of RL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…The loperamide‐induced constipation rat model was established according to previous study (Lee et al., 2012; Lee et al. ; 2020; Li et al., 2021; Wang et al., 2020). The rats of LOP group and three QCT groups were subcutaneously injected with loperamide (3 mg/kg∙body weight, dissolved in saline) twice a day for 3 days, and the rats of Ctrl group were injected with the same volume of saline.…”
Section: Methodsmentioning
confidence: 99%
“…The loperamide‐induced constipation rat model was established according to previous study (Lee et al., 2012; Lee et al. ; 2020; Li et al., 2021; Wang et al., 2020). The rats of LOP group and three QCT groups were subcutaneously injected with loperamide (3 mg/kg∙body weight, dissolved in saline) twice a day for 3 days, and the rats of Ctrl group were injected with the same volume of saline.…”
Section: Methodsmentioning
confidence: 99%
“…Previous data showed that ramie leaf contained polyphenols and flavonoids which were considered excellent antioxidant ( Lee et al, 2014 ). They could effectively activate the antioxidant enzymes in intestinal mucosa ( Lee et al, 2020 ) and muscle tissue ( Li et al, 2019 ). In the current study, 6 and 12% ramie supplementation in diets increased the serum activity of SOD and content of GSH compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal transit time of the feed consumed by the rats was measured using a method described previously 58 . The animals were housed in the fasted state for 12 h after day 6.…”
Section: Methodsmentioning
confidence: 99%